Pengaruh Pengumuman Pembatasan Aktivitas Masyarakat dan Restrukturisasi Kredit terhadap Tingkat Bunga Antar Bank - Murharsito, Murharsito (Balance Vocation Accounting Journal, 2022)
This study aimed to analyze the effect of public activity restriction announcements and credit restructuring on interbank interest rates in Indonesia during the Covid-19 pandemic. This study used the event study method by analyzing changes in interbank interest rates 5 days before and after the announcement event. The announcement of restrictions on community activities consisted of the announcement of the first Covid-19 case in Indonesia, the first PSBB, the second PSBB and emergency PPKM. Meanwhile, the announcement of credit restructuring consisted of a presidential announcement regarding credit relief, the Minister of Finance regarding MSME credit relief and the Chairman of the OJK regarding extending credit relaxation. From the results of the analysis, only the announcement of the minister of finance regarding MSME credit relief had an effect on interbank interest rates.